The response of three storey and eight storey irregular building with set back under earthquake excitation with vertical component - Tan Miao Gin (School of Environmental Engineering, University Malaysia Perlis, 2014)
This paper presents an extensive parametric study on the response of 3 storey and 8 storey set back reinforced concrete (RC) planar frames which are subjected to 10 selected ground motions which recorded by PEER (Pacific Earthquake Engineering Research). Where vertical and horizontal motion, in the range of 0 to 30km. Among 10 ground motion, 5 of the ground motions are in V/H < 1 and the others 5 ground motions are in V/H >1.